Estudio de factibilidad para la implementación de un sistema avanzado de medición (AMI) en clientes de tarifa general con demanda de la Empresa Eléctrica Riobamba S.A - Pazmiño Cisneros, Carlos Andres (2022)
Empresa Eléctrica Riobamba S.A., currently in its concession area has a manual measurement system for large customers, causing involuntary errors in taking readings, accumulated consumption, typing error, display and manipulation of information, generating inconveniences for customers and for the company that has to settle any type of claim. This research project seeks to establish a feasibility study for the implementation of an advanced measurement system (AMI) in general rate customers with demand, to improve business processes, among which are Readings and Billing, as the main beneficiaries. ensuring an adequate quality of the readings for the monthly billing, this study is based on the investigation of the current situation of the Riobamba Electric Company along with the presentation of 3 proposals for AMI systems that may be applicable according to the technical conditions necessary for proper functioning, the proposal to apply an intelligent metering system with a communication system via GPRS being the one that presents a greater economic benefit than with the other 2 proposals, because there is no need to implement a communication infrastructure that supports it. offered by telecommunication companies.